2014
DOI: 10.1007/s00414-014-1073-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a skull/brain model for military wound ballistics studies

Abstract: Reports on penetrating ballistic head injuries in the literature are dominated by case studies of suicides; the penetrating ammunition usually being .22 rimfire or shotgun. The dominating cause of injuries in modern warfare is fragmentation and hence, this is the primary threat that military helmets protect the brain from. When helmets are perforated, this is usually by bullets. In combat, 20% of penetrating injuries occur to the head and its wounding accounts for 50% of combat deaths. A number of head simulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Smith et al [10] found that spheres filled with ballistic gelatine produced damage patterns that compared well with published examples of real gunshot trauma, similar to the findings of both Thali et al [7] using spheres and Carr et al [11] using synthetic skulls. In this present work, the overall fracture patterns in 23 of the 39 skulls (59%) were considered close to reality by at least one of the five assessors.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Smith et al [10] found that spheres filled with ballistic gelatine produced damage patterns that compared well with published examples of real gunshot trauma, similar to the findings of both Thali et al [7] using spheres and Carr et al [11] using synthetic skulls. In this present work, the overall fracture patterns in 23 of the 39 skulls (59%) were considered close to reality by at least one of the five assessors.…”
Section: Discussionsupporting
confidence: 65%
“…A thin low-density polyethylene bag was inserted into the base of the skull and gelatine, 10% by mass, poured into the bag to fill the cranial cavity. The gelatine was allowed to set for 24 h at 17 °C (laboratory temperature) and then conditioned at 4 °C for a further 24 h [11]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and 7.62 mm calibres) were noted to 'compare favourably with published examples of modern cranial gunshot injury' [7]. Carr et al [8] reported similar findings using an anatomically correct skull model which has been the basis for our subsequent experiments [9,10].…”
Section: Introductionsupporting
confidence: 73%
“…Cranial sutures (the joints between the bones of the skull) are able to absorb force, and can stop the progression of fractures across the surface of the cranium (Lovell 1997: 155; Wedel & Galloway 2014: 135). The skull is also buttressed with arched areas of thicker bone; fractures follow the path of least resistance and can be influenced by these patterns of strong and weak bone in the skull (Lovell 1997: 155; Kasrai et al 1999: 238; Wedel & Galloway 2014: 141; Carr et al 2015: 508).…”
Section: Blunt Force Traumamentioning
confidence: 99%